Nonseparable Uhf Algebras Ii: Classification - Farah, Ilijas; Katsura, Takeshi (MATHEMATICA SCANDINAVICA, 2015)
For every uncountable cardinal κ there are 2^κ nonisomorphic simple AF algebras of density character κ and 2^κ nonisomorphic hyperfinite II_1 factors of density character κ. These estimates are maximal possible. All C*-algebras that we construct have the same Elliott invariant and Cuntz semigroup as the CAR algebra.